Quilombo do Lajeado, Dianópolis – TO: uma análise do relatório técnico de identificação e delimitação (RTID) - Silveira, Silvio Silva (2023)
The objective of this work is to understand the formation of Lajeado Quilombo, located in the municipality of Dianópolis - TO. That done, we will address the existing legislation on the subject. To this end, we will take as its starting point Article 68 of the acts of the Transitional Constitutional Provisions (ADCT) of the Federal Constitution of 1988, historically contextually the inclusion of public policy of the recognition and demarcation of quilombola territories in the 1988 Citizen Charter. This research It also aims to problematize the main aspects of the Technical Identification and Demarcation Report (RTID) of the Quilombola do Lajeado community, located in the municipality of Dianópolis - TO, in order to understand and identify the elements that characterize that people as quilombola. We then describe and problematize the history of the quilombola territory of Lajeado, having as temporal cut the post-2005 period, from when the community mobilized in the search for recognition of its condition. The main source for our research was the aforementioned RTID, especially its second volume, where the anthropological report is located. In addition to a documentary analysis, bibliographic, legislative research and data analysis provided by public agencies were also constituted in important sources for this research. Finally, the present work addresses aspects of the customs and material culture of the community and the possibility of appropriation of these elements in the practical and symbolic field as a resistance support from the community itself to the challenges faced in their daily lives.